Machining of Bone and Hard Tissues - Dahotre, Narendra B.; Joshi, Sameehan S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides an in-depth review of state-of-the-art orthopaedic techniques and basic mechanical operations (drilling, boring, cutting, grinding/milling) involved in present day orthopaedic surgery. Casting a light on exploratory hybrid operations, as well as non-conventional techniques such as laser assisted operations, this book further extends the discussion to include physical aspects of the surgery in view of material (bone) and process parameters. Featuring detailed discussion of the computational modeling of forces (mechanical and thermal) involved in surgical procedures for the planning and optimization of the process/procedure and system development, this book lays the foundations for efforts towards the future development of improved orthopaedic surgery. With topics including the role of bone machining during surgical operations; the physical properties of the bone which influence the response to any machining operation, and robotic automation, this book will be a valuable and comprehensive literature source for years to come.
Introduction -- Fundamental Operations of Bone Machining -- Non-conventional and Hybrid Methods of Bone Machining -- Attributes of Bone Machining -- Computational Modeling in Bone Machining -- Potential Automation of bone Machining.
Keywords: Biomaterials; Orthopedic surgery; Manufactures; Control engineering; Robotics; Automation; Biotechnology; Endoscopic surgery; Biomaterials; Surgical Orthopedics; Machines, Tools, Processes; Control, Robotics, Automation; Biotechnology; Minimally Invasive Surgery